2006
DOI: 10.1002/cbf.1355
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of L‐carnitine on testicular ischaemia–reperfusion injury in rats

Abstract: Testicular torsion is a urological emergency referred to as 'acute scrotum', because inappropriate treatment can lead to male subfertility and infertility. A possible cause of testicular damage is the ischaemia-reperfusion (I/R) injury attributed to oxygen free radicals. L-carnitine, a vitamin-like antioxidant, plays a pivotal role in the maturation of spermatozoa within the reproductive tract. The aim of the present paper was to determine the protective effect of L-carnitine on testicular I/R-induced injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 38 publications
2
48
2
1
Order By: Relevance
“…[31] It has been clearly revealed that reperfusion of the ischemic tissue is associated with oxidative stress. [32] Therefore, treatment by detorsion may further damage the testes. ROS are short-lived reactive molecules having one or more unpaired electrons, rendering them highly unstable and highly reactive.…”
Section: Discussionmentioning
confidence: 99%
“…[31] It has been clearly revealed that reperfusion of the ischemic tissue is associated with oxidative stress. [32] Therefore, treatment by detorsion may further damage the testes. ROS are short-lived reactive molecules having one or more unpaired electrons, rendering them highly unstable and highly reactive.…”
Section: Discussionmentioning
confidence: 99%
“…17,[55][56][57] In addition, the tissue injury induced by testicular torsion/detorsion can be dramatically alleviated by pretreatment with exogenous antioxidants such as selenium, resveratrol, L-carnitine, caffeic acid phenethyl ester and garlic extract. 17,[57][58][59][60] Finally the enzyme purportedly associated with reperfusion injury, xanthine oxidase, can be inhibited by allopurinol and the latter is known to reduce the testicular damage associated with testicular torsion. 56 Notwithstanding the importance of xanthine oxidase-mediated oxidative stress it should also be noted that neutrophil infiltration into the testes following torsion may represent yet another source of uncontrolled free radical generation responsible for mediating the pathophysiological consequences of temporary testicular ischaemia.…”
Section: Small Molecular Mass Antioxidantsmentioning
confidence: 99%
“…Typically this model involves the application of antioxidant therapy prior to the creation of a brief period of oxidative stress and subsequent comparison of various testicular attributes (lipid peroxidation, histopathology, DNA damage or antioxidant enzyme status) with sham operated controls ( Table 2). Such analyses have recorded significant protection against oxidative stress for factors as garlic extract, 57 caffeic acid phenethyl ester (CAPE), 60 N-acetyl cysteine, 158 pentoxifylline, 159 erdostein, 160 resveratrol, 58 dexpathenol, 161 L-carnitine 59 and propofol anaesthetic. 162 A variety of antioxidants have also been assessed for their ability to counteract oxidative stress in the testes created by alternative mechanisms.…”
Section: Antioxidant Therapymentioning
confidence: 99%
“…One animal study examined the effect of L-carnitine on testicular ischaemic reperfusion injury in rats (Dokmeci et al, 2007). The Panel considers that evidence provided in animal studies is not sufficient to predict the occurrence of an effect of L-carnitine consumption on spermatogenesis in humans.…”
Section: Contribution To Normal Spermatogenesis (Id 1822)mentioning
confidence: 99%